2022
DOI: 10.1021/acs.jpclett.2c02119
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Mechanisms or Chemical Mechanisms? Role of Interfacial Charge Transfer in the Plasmonic Metal/Semiconductor Heterojunction

Abstract: The plasmonic metal/semiconductor heterojunction provides a unique paradigm for manipulating light to improve the efficiency of plasmonic materials. Previous studies suggest that the improvement originates from the enhanced carrier exchanges between the plasmonic component of the heterojunction and molecules. This viewpoint, known as the chemical mechanism, is reasonable but insufficient, because the construction of the heterojunction will lead to a charge redistribution in the plasmonic component and cause ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Besides the field coupling, there exists another enhanced mechanism that relies on the transferring of excited electrons [ 35 , 36 , 37 ]. Under proper excitation, the resonant surface electrons of Au particles can be transferred to R6G molecules, promoting the molecular vibration, which in turn increased the scattering cross-section, and consequently, Raman scattering effect was enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the field coupling, there exists another enhanced mechanism that relies on the transferring of excited electrons [ 35 , 36 , 37 ]. Under proper excitation, the resonant surface electrons of Au particles can be transferred to R6G molecules, promoting the molecular vibration, which in turn increased the scattering cross-section, and consequently, Raman scattering effect was enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…The authors suggested that the additional enhancement originates from oxygen vacancy defects on TiO 2 surfaces generated by pre-irradiation, namely, the vacancy species below the conduction bond edge enabled electrons to be excited into the conduction bond and then transferred into metal energy levels upon Raman laser illumination, leading to a stronger local electromagnetic field of metal NPs. 196,246 Besides inorganic semiconductors, organic semiconductors can also be used to combine with plasmonic metals for PIERS applications. Almohammed et al demonstrated that the UV-induced charge transfer in the substrate of Ag nanoparticle-decorated aligned diphenylalanine peptide nanotubes (FF-PNTs) facilitated CM that provided up to a 10-fold increase in SERS intensity and allowed the detection of a wide range of small molecules and low Raman cross-section molecules at concentrations as low as 10 −13 M. 243…”
Section: Nanocomposites Consisted Of Metal and Sers-active Nonmetal N...mentioning
confidence: 99%
“…We note that the observed additional boost in signal intensity can also be partially attributed to the increased EM enhancement resulting from the injection of electron density from the SnO 2 to the Au NTs via band alignment. 43 Moreover, the hybrid SERS signals were shown to be highly stable over long timeframes, due to the intrinsic nature of the oxygen vacancies and the aggregation-free approach of the sensing scheme.…”
Section: Hybrid Sers With Stable Enhancement In Aqueous Mediamentioning
confidence: 99%